2020
DOI: 10.29219/fnr.v64.3677
|View full text |Cite
|
Sign up to set email alerts
|

Soybean protein-derived peptide nutriment increases negative nitrogen balance in burn injury-induced inflammatory stress response in aged rats through the modulation of white blood cells and immune factors

Abstract: Background: As an important nutrient, soybean protein-derived peptides (SPP) affect the immune function of animals. Objective: This study describes the effects of nutrient supplementation with SPP on the negative nitrogen balance in the burn injury-induced inflammatory response of aged rats. Design: Soybean protein isolate (SPI) was hydrolyzed to obtain SPP. A negative nitrogen-balance aged rat model and a major full-thickness 30% total body surface area (TBSA) burn-injury rat model were utilized. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…SPs currently in market have diverse applications such as in sports drinks, meal replacements, diet meals, and health supplements. SP material market has recently been experiencing rapid global growth as consumers have become increasingly aware of the benefits of soy peptides, including its nutritional and physiological effects, effects on physical fatigue related to absorption rate and sports nutrition, and effect on psychological fatigue related to stress [10,151,155]. In particular, the main attraction of products containing SPs currently available in market is fatigue recovery.…”
Section: Economic Feasibility and Application Of Soybean-derived Bioactive Peptidesmentioning
confidence: 99%
“…SPs currently in market have diverse applications such as in sports drinks, meal replacements, diet meals, and health supplements. SP material market has recently been experiencing rapid global growth as consumers have become increasingly aware of the benefits of soy peptides, including its nutritional and physiological effects, effects on physical fatigue related to absorption rate and sports nutrition, and effect on psychological fatigue related to stress [10,151,155]. In particular, the main attraction of products containing SPs currently available in market is fatigue recovery.…”
Section: Economic Feasibility and Application Of Soybean-derived Bioactive Peptidesmentioning
confidence: 99%
“…Liver is a dynamic organ in serum protein synthesis, gluconeogenesis, lipogenesis, and cholesterol metabolism ( 28 ). Serum TP and ALB are regarded as the important indicators of the protein metabolism, and decreased serum TP and ALB concentrations is usually related to malnutrition and growth retardation in animals ( 29 , 30 ). The serum level of GLU is an indicator of glycolipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al ( 40 ) found that supplementation of aureomycin reduced serum concentrations of TNF-α, IL-2, and IL-6 in broiler chickens. The immune response is controlled by the complex interaction of various cytokines, and pro-inflammatory factors IL-6 and IL-1β have been used as markers of the inflammatory response ( 29 ). IL-1β plays a decisive role in the production of pro-inflammatory and homeostatic functions ( 41 ), while IL-6 is a multifunctional cytokine that can participate in the regulation of body inflammation, hematopoiesis, immune response, and acute phase response ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular weight distribution of Se‐SPep was determined following a previously reported method (Zhang, Li, et al., 2020 ). The standard molecular weight samples containing aprotinin (6500 Da), bacitracin (1422 Da), and Gly–Gly–Tyr–Arg (451 Da) were passed through 0.22 μm filters and successively loaded into a Superdex 200 10/300 GL column.…”
Section: Methodsmentioning
confidence: 99%